Dynamic structural characteristics and vibration susceptibility of Tongren loess under the influence of water content and confining pressure - Changbao Guo; Sanshao Ren; Yinlong Tan; Yaqi Shen (Scientific Reports)
Abstract Loess is extensively developed on both sides of the Longwu River, a tributary of the Yellow River, Tongren County, Qinghai Province. The engineering geological characteristics are complex, and landslide disasters are highly developed. Based on field geological surveys and physical property analysis of the loess in this area, this study analyzes the influence of water content, consolidation pressure, and soil disturbance on the dynamic characteristics of loess using GDS dynamic triaxial tests. The results show that Tongren loess has strong structural properties. Its dynamic constitutive relationship conforms to the Hardin-Dinevich hyperbolic model, where the parameters a and b decrease with increasing confining pressure and increase with increasing water content. The dynamic cohesion and dynamic friction angle both decrease with increasing water content, with the dynamic cohesion significantly affected, decreasing by 77% ~ 83% when saturated. However, the dynamic friction angle is less affected by water content changes, decreasing by 18% ~ 25% when saturated. Under dynamic conditions, the dynamic friction angle of Tongren loess is only 12 ~ 16°, making slopes composed of Tongren loess highly susceptible to instability and sliding under strong earthquake conditions. The dynamic structural properties of Tongren loess are significantly influenced by water content, with increasing water content destroying the joint structural strength of intact loess. Before reaching the plastic limit water content, the joint structural strength of intact loess decreases sharply with increasing water content, and then decreases slowly. The frictional structural strength shows an opposite trend. Under the same experimental conditions, the failure dynamic stress, maximum dynamic elastic modulus, and dynamic shear strength parameters of intact loess are generally greater than those of remolded loess, and the differences between them decrease with increasing water content. This study provides insights into the dynamic structural characteristics of Tongren loess, which can serve as a reference for understanding the formation mechanisms, stability analysis, and seismic design of loess landslides in the region.